A residualidade na cordelística de Medeiros Braga e o seu papel nas salas de aula da Educação Básica - Marinho, Jovanna Pinheiro Medeiros (2022)
The main goals of this work are to address the residual aspects present in Medeiros Braga's cordelistics and to emphasize its important role in basic education classrooms. Medeiros Braga's strings present various themes and resources that facilitate students' learning about universal themes necessary for everyone's social formation. From the analysis of his cordéis and in the light of Roberto Pontes' theory of residuality , we identify Christian, historical and medieval aspects that make us believe that Medeiros Braga used past mentalities in the construction of his poetry and crystallizes them in cordel leaflets using a language peculiar and critical to create spaces, times and reflections that make them a rich material of popular culture, as well as of didactic pedagogical involvement that contribute significantly to their applicability in classrooms, thus praising their productions as important educational instruments that provide necessary improvements in the teaching and learning process for students from the most diverse social classes.